Heterogeneity of ILC2s in the Intestine; Homeostasis and Pathology - Sunaga, Shogo; Tsunoda, Junya; Teratani, Toshiaki; Mikami, Yohei; Kanai, Takanori (Frontiers in Immunology, 2022)
Group 2 innate lymphoid cells (ILC2s) were identified in 2010 as a novel lymphocyte subset lacking antigen receptors, such as T-cell or B-cell receptors. ILC2s induce local immune responses characterized by producing type 2 cytokines and play essential roles for maintaining tissue homeostasis. ILC2s are distributed across various organs, including the intestine where immune cells are continuously exposed to external antigens. Followed by luminal antigen stimulation, intestinal epithelial cells produce alarmins, such as IL-25, IL-33, and thymic stromal lymphopoietin, and activate ILC2s to expand and produce cytokines. In the context of parasite infection, the tuft cell lining in the epithelium has been revealed as a dominant source of intestinal IL-25 and possesses the capability to regulate ILC2 homeostasis. Neuronal systems also regulate ILC2s through neuropeptides and neurotransmitters, and interact with ILC2s bidirectionally, a process termed “neuro-immune crosstalk”. Activated ILC2s produce type 2 cytokines, which contribute to epithelial barrier function, clearance of luminal antigens and tissue repair, while ILC2s are also involved in chronic inflammation and tissue fibrosis. Recent studies have shed light on the contribution of ILC2s to inflammatory bowel diseases, mainly comprising ulcerative colitis and Crohn’s disease, as defined by chronic immune activation and inflammation. Modern single-cell analysis techniques provide a tissue-specific picture of ILC2s and their roles in regulating homeostasis in each organ. Particularly, single-cell analysis helps our understanding of the uniqueness and commonness of ILC2s across tissues and opens the novel research area of ILC2 heterogeneity. ILC2s are classified into different phenotypes depending on tissue and phase of inflammation, mainly inflammatory and natural ILC2 cells. ILC2s can also switch phenotype to ILC1- or ILC3-like subsets. Hence, recent studies have revealed the heterogeneity and plasticity of ILC2, which indicate dynamicity of inflammation and the immune system. In this review, we describe the regulatory mechanisms, function, and pathological roles of ILC2s in the intestine.